Transplantation in the opinion of operating nurses - Majchrowicz, Bożena (Journal of Education, Health and Sport, 2022)
Transplant surgery has become the standard method of treating many diseases that were fatal until recently. Doubts in this matter, regardless of the effectiveness of this method of saving human life, still exist in the public opinion. There are still stereotypes that inhibit the development of transplantology as a field of science. The aim of the research was to present the opinions of the surveyed operating nurses on transplantation Material and methods: The research was conducted on social networks in a group associating operating nurses in January and February 2021. 193 medical nurse nurses participated in them. The research method was a diagnostic survey and the tool was the original questionnaire. During the statistical analysis, the Chi2 test as well as the Kendall Tau-b and Kendall Tau-c correlations were used to check the significance of the relationship between the variables built on the qualitative scales. Results and conclusions: 95.1% of the surveyed nurses considered transplantation saving lives. 49.5% of the respondents believe that the best way to regulate the procurement of organs for transplantation is consent given in life. An equally large group of respondents, 34.0%, say that it is enough not to object while living. The respondents support the transplant procedure due to their high awareness in this regard. They know that transplant operations save people's lives and are safe for living donors.